Macrophage‐derived HMGB1 is dispensable for tissue fibrogenesis. Issue 4 (12th February 2019) - Personnaz, Jean; Piccolo, Enzo; Branchereau, Maxime; Filliol, Aveline; Paccoud, Romain; Moreau, Elsa; Calise, Denis; Riant, Elodie; Gourdy, Pierre; Heymes, Christophe; Schwabe, Robert F.; Dray, Cédric; et al.
Abstract: Alarmins and damage‐associated molecular patterns (DAMPs) are powerful inflammatory mediators, capable of initiating and maintaining sterile inflammation during acute or chronic tissue injury. Recent evidence suggests that alarmins/DAMPs may also trigger tissue regeneration and repair, suggesting a potential contribution to tissue fibrogenesis. High mobility group B1 (HMGB1), a bona fide alarmin/DAMP, may be released passively by necrotic cells or actively secreted by innate immune cells. Macrophages can release large amounts of HMGB1 and play a key role in wound healing and regeneration processes. Here, we hypothesized that macrophages may be a key source of HMGB1 and thereby contribute to wound healing and fibrogenesis. Surprisingly, cell‐specific deletion approaches, demonstrated that macrophage‐derived HMGB1 is not involved in tissue fibrogenesis in multiple organs with different underlying pathologies. Compared to control HMGB1 Flox mice, mice with macrophage‐specific HMGB1 deletion (HMGB1 ΔMac ) do not display any modification of fibrogenesis in the liver after CCL4 or thioacetamide treatment and bile duct ligation; in the kidney following unilateral ureter obstruction; and in the heart after transverse aortic constriction. Of note, even under thermoneutral housing, known to exacerbate inflammation and fibrosis features, HMGB1 ΔMac mice do not show impairment of fibrogenesis. In conclusion, our study clearly establishes that macrophage‐derived HMGB1 does not contribute to tissue repair and fibrogenesis.